The Rohingya Crisis: Regional Security Implications - Jasminder Singh (2017)
After the border attacks in Maungdaw by Muslim militants, the Tatmadaw (Myanmar national army) has been accused of raping and killing Rohingya and burning their villages by the media and human rights groups. This has rekindled pro-Rohingya jihadist sentiments in the region as well as globally.